Technical Analysis: Power Tools for Active Investors. - Appel, Gerald (FT Press Pearson Education [distributor], 2005)
Unlike most technical analysis books, Gerald Appel's Practical Power Tools! offers step-by-step instructions virtually any investor can use to achieve breakthrough success in the market. Appel illuminates a wide range of strategies and timing models, demystifying even advanced technical analysis the first time. Among the models he covers: NASDAQ/NYSE Relative Strength, 3-5 Year Treasury Notes, Triple Momentum, Seasonality, Breadth-Thrust Impulse, and models based on the revolutionary MACD techniques he personally invented. Appel covers momentum and trend of price movement, time and calendar cycles, predictive chart patterns, relative strength, analysis of internal vs. external markets, market breadth, moving averages, trading channels, overbought/oversold indicators, Trin, VIX, major term buy signals, major term sell signals, moving average trading channels, stock market synergy, and much more. He presents techniques for short-, intermediate-, and long-term investors, and even for mutual fund investors.